Hubungan antara tingkah laku asertif dengan komitmen organisasi dalam kalangan staf sokongan Universiti Tun Hussein Onn Malaysia (UTHM) - Omar, Hawa (2014)
This study aims to examine the relationship between assertive behavior and organizational commitment among support staffs at Universiti Tun Hussein Onn Malaysia (UTHM), Pt. Raja, Batu Pahat, Johor. This study involves a total of 202 nonacademic staffs under the classification of administrative and support services (N) consisting of the Support Group I (Grade N27 to N40) and the Support Group II (Grade N17 to N26 ) in operational group type scheme of service, according to Malaysian Remuneration System (SSM), the Public Service Department of Malaysia. This is a quantitative study and questionnaire was used as an instrument. Rathus Assertive Questionnaire (1973) was used to measure assertive behavior, while Organizational Commitment Questionnaire Allen and Meyer (1990) was used to measure organizational commitment. The collected data were analyzed using the Statistical Package for the Social Science (SPSS) Version 19.0. Findings indicated that the level of assertive behavior and commitment of UTHM‘s support staffs are moderate. Pearson correlation analysis showed a significant positive relationship at low levels of assertive behavior with organizational commitment. Meanwhile, the Standard Multiple Regression Analysis showed that the dimension of assertive behavior, the Ability to Sustain a Stand (KP) is the most dominant in influencing organizational commitment among UTHM‘s support staffs.